Dinámicas de género en el mercado crediticio en los hogares colombianos de bajos recursos (2017)
The present investigation aims to analyze gender dynamics of access to the Colombian credit market of low income households. In particular, it focuses on analyzing whether gender is a determinant of the amount and number of loans obtained. For this, the second round of the Colombian Longitudinal Survey of the University of Los Andes (ELCA 2013) is used, and an estimations are made using the two stages Heckman methodology in order to correct the self-selection bias that comes from the endogeneity of the actions of requesting and receiving credits. This research is highly relevant to economic literature given that women's access to the financial market provides them with economic autonomy and greater decision-making power in the household, which has effects on the well-being of their household, insofar as, according to the economic literature Reviewed, women have a better management of resources than men in terms of child nutrition, human capital investment and financial responsibility (Khandker, Pitt, Chowdhury, Millimet, 2003). The results show that in households where there is a single head of household and is a female, have a higher number of credits granted; However, when disaggregating by formality of the credits, it results that the females heads of households have more informal credits than mens that are heads of households. Likewise, there is no significant evidence to determine a differential in the amounts granted to womens and mens heads of households.--Tomado del Formato de Documento de Grado.